Pre-employment assessment, training and counselling for usually handicapped persons in Asia. - Hilde, Groth (Universiti Kebangsaan Malaysia, 1975)
This article present a methodology for providing individualized client-centered rehabilitation service for the severely visually handicapped in Malaysia and other Asian countries. Illustrative results are presented and specific needs that will make rehabilitation programs more successful both for the individual and the society have been discussed.